Sick at work: prevalence and determinants among healthcare workers, western Ethiopia: an institution based cross-sectional study - Tesfaye Hambisa Mekonnen; Mekuriaw Alemayewu Tefera; Yayehirad Alemu Melsew (Annals of Occupational and Environmental Medicine, 2018)
Abstract Background Going to work despite feeling sick also known as sickness presenteeism is one of the emerging global occupational health challenges. Sickness presenteeism negatively affects both health of work forces and productivity of organizations in general. However, there is insufficient research exploring this situation in majority of the Sub-Saharan African countries, including Ethiopia. Thus this study intended to investigate the prevalence and determinant factors of sickness presenteeism among health care workers, Western Ethiopia. Methods This study used an institution based cross-sectional quantitative study design. The study period was from February to March, 2017. We employed simple random sampling method to select 360 study samples. Data collection was performed by pre-tested structured and self- administered questionnaire. We used SPSS version 20 to carry out binary logistic regression analysis. Odds ratio with 95% confidence intervals was calculated and significance of associations was determined at p-value < 0.05. Results A total of 344 respondents fully completed the survey questionnaire. Mean age with standard deviation was 30.28 ± 6.181. Prevalence of sickness Presenteeism was 52.6% [95%CI: (47.4, 57.8)] in the past 12 months. Educational status [AOR:2.1, 95%CI: (1.17,3.90)], financial problem [AOR:1.9,95%CI:(1.07,3.46)], sickness absenteeism [AOR:2.7,95% CI:(1.50,5.02)], lack of staff replacement [AOR:2.7,95%CI:(1.50,5.02)], absence of occupational health services [AOR:3.0,95%CI:(1.34,6.70)], and pressure from supervisor [AOR:1.8,95% CI:(1.01,3.31)] were significant predictors of the dependent variable. Conclusion Relatively higher proportions of workers indicated sickness presenteeism as compared to other studies. Risk factors like educational status, personal financial problem, sickness absenteeism, lack of staff replacement, absence of occupational health services, and pressure from supervisors considerably increased the likely occurrence of employees’ sick attendance. It is advisable for health care managers to hire adequate health care staffs, to implement basic occupational health services and to design strategies which reduce pressure from supervisors.